Risk Factors and Characteristics Associated with Visual Impairment and Eye Diseases in Moyamoya Disease: Insights from a National Database - Youyi Song; Xin Yang; Hongzhu Yang; Hongyun Mei; Xuedan Lu; Hao Xie; Qinfeng Yang; Wenbin Duan (Ophthalmology and Therapy)
Abstract Introduction This study aims to investigate the incidence and risk factors of visual impairment and eye diseases in patients with moyamoya disease (MMD), a rare cerebrovascular disorder. Understanding these associations is crucial for improving patient management and outcomes. Methods This study utilized International Classification of Diseases (ICD) codes from both the 9th edition (ICD-9-CM) and 10th edition (ICD-10-CM) to define diagnoses, complications, and procedures within the National Inpatient Sample (NIS) Database. Data elements were extracted from discharge summaries. Statistical analysis was performed using IBM SPSS Statistics software version 25. Chi-square tests were employed for univariate analysis to assess the relationships between visual impairment, eye diseases, and MMD. Subsequently, multivariate logistic regression was utilized to calculate odds ratios (OR) and their corresponding 95% confidence intervals (CI) over a 10-year period to further investigate these relationships. Results The incidence of visual impairment and eye diseases in MMD was 3.7%. Visual impairment and eye diseases in MMD were associated with Asian or Pacific Islander race (OR = 1.538, 95% CI 1.058–2.237), self-pay insurance (OR = 1.796, 95% CI 1.503–3.061), and hospitalization in the Midwest or North Central region (OR = 1.466, 95% CI 1.035–2.076). Visual impairment and eye diseases in moyamoya disease were associated with ischemic stroke (OR = 2.001, 95% CI 1.564–2.560), hypertension (OR = 1.508, 95% CI 1.089–2.088), headache (OR = 2.834, 95% CI 1.968–4.081), migraine (OR = 2.156, 95% CI 1.544–3.011), memory loss (OR = 3.866, 95% CI 1.493–10.012), and dizziness (OR = 1.322, 95% CI 0.549–3.182). Conclusions Our analysis of a large, population-based sample in the US reveals a notable association between MMD and the presence of visual impairment and eye diseases.